The role of epigenetic factors in the pathogenesis of familial X-linked mental retardation (XLMR) - Carvill, Gemma (Division of Human Genetics, 2014)
Mental retardation (MR) is a handicap with severe implications not only for thosethat suffer from this disability, but also for their families, society and the welfaresystems which support them. A large proportion of these individuals are afflictedwith the X-linked form of the condition. To date a total of 87 genes have beenimplicated in the pathogenesis of X-linked mental retardation (XLMR).